Antithrombin I. Inhibition of thrombin generation in plasma by fibrin formation - Mosesson, Michael W. (Thrombosis and Haemostasis, 2003)
Thrombin substrate binding is mediated through fibrinogen recognition “exosite 1” in thrombin, resulting in fibrinopeptide cleavage to form fibrin. In addition, thrombin exhibits “non-substrate” binding to fibrin, an activity termed “Antithrombin I”. Antithrombin I (AT-I) is characterized by two classes of throm-bin binding sites, the first of “low affinity” in the fibrin E domain, and the other of high affinity, that is situated between C-terminal residues 414 and 427 of a variant γ chain termed γ’ 1-427L. Plasma fibrinogen molecules containing γ ’ chains (“fibrino-gen 2”) are virtually all heterodimers containing one γA chain (platelet-binding) and one γ’ chain. The remaining fibrinogen (~ 85%) is homodimeric, lacks high affinity thrombin-binding potential, and is termed “fibrinogen 1” (γA/γA). Thrombin generation in recalcified fibrinogen-depleted or congenital afibrinogenemic plasma is increased. Repletion with fibrino-gen 1 has a modest effect in normalizing thrombin generation, whereas repletion with fibrinogen 2 (γA/γ’) has a more marked effect. A post-translational γ’ chain derivative, γ’ 1-423P, accounts for 3%-34% of the γ’ chain population, lacks thrombin binding potential, and arises by proteolytic processing at the expense of γ’ 1-427L chains. Little is known about its effect on plasma AT-I activity under normal or pathological circumstances. In summary, fibrin formation (Antithrombin I) inhibits throm-bin generation in clotting blood by sequestering thrombin, and “high-affinity” thrombin-binding (i.e., via γ’ chains) plays a dominant role in this process. AT-1 should be considered when assessing the pathogenesis of thromboembolic disease.
Keywords: Fibrin; thrombin; antithrombin; thrombin inhibition